From competencies to action: unpacking the path from students' sustainability competencies to self-reported prosocial behavior - Katarzyna Piwowar-Sulej; Katarzyna Tracz-Krupa; Vincent Cassar; Frank Bezzina (Frontiers in Psychology, 2026)
Introduction Achieving social sustainability requires a deeper understanding of how individual competencies are associated with active prosocial actions. This cross-sectional study examined the associations between higher education students' key competencies in sustainability (KCiS) and their self-reported prosocial behavior, focusing on the mediating role of prosocial norms, and the moderating influence of individual cultural orientations (horizontal and vertical collectivism). Methods Grounded in Norm-Activation Theory and informed by Social Learning Theory, structural equation modeling (SEM) and bootstrap moderated mediation analysis were conducted on survey data from 883 university students across five European universities. Results Results indicated that prosocial norms indirectly connected KCiS with prosocial behavior. Contrary to expectations, horizontal collectivism did not moderate the direct or indirect pathways. However, a significant negative interaction emerged: vertical collectivism attenuated the positive association between KCiS and prosocial norms, with the conditional indirect association weakening at higher levels of vertical collectivism. Discussion Testing conditional indirect associations revealed a dampening pattern that standard bivariate models overlook. Contextualized by self-reported data, these findings demonstrate how sustainability competencies and cultural variations relate to prosocial action, offering theoretical insights into cultural boundary conditions and informing targeted higher education strategies.